ANALISIS KESALAHAN BERBAHASA DALAM BERITA “10 KARUNG CD WANITA DIDUGA PEZIARAH BERSERAKAN DI NAGARA PADANG CIWIDEY” - Aspa Aspia; Diny Mar’ah Hanifah (Populer: Jurnal Penelitian Mahasiswa, 2022)
Indonesian as the language of unity and national identity must be upheld, namely by learning and using good and correct Indonesian. However, we often encounter language errors in newspapers, especially news on social media. The purpose of this study is (1) to describe language errors in terms of spelling, morphology and semantics contained in detik.com news; (2) to provide corrections for language errors in terms of spelling, morphology and semantics contained in detik.com news. This research is a descriptive qualitative research. The data collection technique used in this study is the observation and note taking technique. The use of the listening technique is carried out by listening to the data on the use language and the note taking technique is carried out with what forms of language errors are made and analyzing according to the form of the error. The results of the analysis of the analysis of language errors in detik.com news October 2022 edition can be concluded that there is a form of error in the news title 10 Sacks of CD Allegedly Pilgrims Scattered in Nagara Padang Ciwidey Here there is ambiguity in the choice of words for the news title, error standard word, spelling errors, punctuation errors, affix errors and capitalization errors.